Reporting of adverse events related to dietary supplements to a public health center by medical staff: a survey of clinics and pharmacies - Ide K; Yamada H; Kawasaki Y; Noguchi M; Kitagawa M; Chiba T; Kagawa Y; Umegaki K (Dove Medical Press, 2016)
Kazuki Ide,1 Hiroshi Yamada,1 Yohei Kawasaki,1 Marika Noguchi,1 Mamoru Kitagawa,1 Tsuyoshi Chiba,2 Yoshiyuki Kagawa,3 Keizo Umegaki2 1Department of Drug Evaluation & Informatics, Graduate School of Pharmaceutical Sciences, University of Shizuoka, Shizuoka, 2Information Center, National Institutes of Biomedical Innovation, Health and Nutrition, Tokyo, 3Department of Clinical Pharmaceutics, Graduate School of Pharmaceutical Sciences, University of Shizuoka, Shizuoka, Japan Background: Dietary supplements are used by >50% of the adult population in Japan, and adverse events related to these products have been reported with their increased use. Thus, an efficient system to gather and report data on these adverse events is essential. To date, however, reporting has been limited. The aim of this study was to address this deficiency by exploring the routine reporting practices of the medical staff employed at clinics or pharmacies in Japan.Methods: We conducted a survey of the procedures used by the medical staff to report adverse events related to dietary supplement intake to public health centers in Japan. The survey was conducted in Japan between November 2015 and January 2016. Based on a sample size calculation, questionnaires were administered to 1,700 potential respondents (850 pharmacists and 850 physicians). The questionnaire inquired about the sociodemographic characteristics and dietary supplement-related adverse event-reporting practices.Results: The response rate was 34.7%, including 286 pharmacists and 304 physicians. Although >30% of the pharmacists and physicians had prior experience dealing with such adverse events, <5% had reported these to a public health center. The survey identified several barriers to reporting, such as “difficulty judging the relationship between an adverse event and the dietary supplement” and “lack of clarity regarding the severity of an adverse event”.Conclusion: This is the first study to explore the routine reporting practices of physicians and pharmacists in terms of adverse events related to dietary supplements. Further studies are required to elucidate the severity of these adverse events. Moreover, standard reporting criteria ought to be introduced to improve public health. Keywords: dietary supplements, complementary medicine, pharmacy practice, government regulations, survey